2012
DOI: 10.3846/bjrbe.2012.04
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Pavement Layers Thickness Measured by Georadar and Conventional Methods – Examples From Croatia

Abstract: Thickness of the pavement structure layers represents an important data for the implementation into the database of roads already constructed, during the pavement strengthening design, particularly if the appraisal of the bearing capacity of the pavement structure is done by means of the Falling Weight Deflectometer, during reconstruction of pavements or during control of the newly constructed roads. If reconstruction is carried out by procedures of recycling of the existing pavement the details about the thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Analysis of the GPR data collected from different sites showed that thickness error increases with pavement age-4.4% error for 0-to 5-year-old pavements and 5.8% error for pavements older than 20 years having surfaces older than 10 years [14]. In Croatia, studies have been conducted on motorways, regional and county roads and on runways [18,19]. The error for new pavements of motorways was mostly less than 10% and varied from 0.16% to 12.32% [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the GPR data collected from different sites showed that thickness error increases with pavement age-4.4% error for 0-to 5-year-old pavements and 5.8% error for pavements older than 20 years having surfaces older than 10 years [14]. In Croatia, studies have been conducted on motorways, regional and county roads and on runways [18,19]. The error for new pavements of motorways was mostly less than 10% and varied from 0.16% to 12.32% [18].…”
Section: Introductionmentioning
confidence: 99%
“…In Croatia, studies have been conducted on motorways, regional and county roads and on runways [18,19]. The error for new pavements of motorways was mostly less than 10% and varied from 0.16% to 12.32% [18]. For regional and county roads that have been in service for years, the error ranges from 6.70% to 14.83% [18].…”
Section: Introductionmentioning
confidence: 99%
“…EM waves partly reflect and partly pass through layers of materials with different EM characteristics. A part of energy that reflects at layers interface is receive by GPR system and displayed as a plot of amplitude (voltage) and time necessary for its return to antenna (Figure 1, right) [2].…”
Section: Description Of Gpr and Fwd Methodsmentioning
confidence: 99%
“…Evaluation studies carried out in the last 20 years show that deviations between GPR and core thickness results of newly constructed pavement range from 2% to 5% of total thickness [1] and for old pavements are mostly less than 10% [2]. Based on this it can be conclude that GPR is suitable non-destructive technique, which can replace coring.…”
Section: Introductionmentioning
confidence: 99%
“…Nondestructive acoustic techniques, especially the state-of-the-art impulse response technique (ASTM C1740-10 2010) and ultrasonic tomography , increasingly and often used today to diagnose building structures, can be helpful in this regard (Schickert 2005;Beutel et al 2008;Maksymowicz et al 2011;Zwolski, Bień 2011;Goszczyńska et al 2012;Leibbrandt et al 2012;Ožbolt et al 2012).…”
Section: Introductionmentioning
confidence: 99%